Biobanks as a way to conserve biodiversity in the context of the continuing decline in the species diversity of wild flora and fauna - Dairov, A.K.; Mukanov , K.K.; Khapilina, O.N.; Manabayeva, Sh.A.; Kakimzhanova, A.A.; Khassenova , A.E.; Kubentayev , S.A.; Zholdybayeva , E.V.; Khassenov , B.B.; Shevtsov , A.B.; Tarlykov , P.V.; Mukantayev , K.N.; et al. (Eurasian Journal of Applied Biotechnology, 2024)
To date, human actions have significantly changed 75% of the Earth’s surface. This has resulted in an unprecedented increase in the rate of biodiversity loss in human history. According to the International Union for Conservation of Nature and Natural Resources, over the past 500 years, as a result of direct or indirect influence of the anthropogenic factor, 774 animal species and 123 plant species have become extinct. To prevent further loss of biodiversity, in the context of the ongoing «crisis of biodiversity», all over the world, including Kazakhstan, there is a need for reliable conservation of the available genetic resources of plants and animals, primarily rare and endangered species. In this regard, specialized biobanks of organized collections of living biomaterials are successfully used worldwide for the conservation and restoration of populations of rare and endangered species of flora and fauna. The article presents information about some of the largest biobanks and their importance in solving this global problem. The experience of scientific centers of Kazakhstan in the field of biobanking of biomaterials of wild flora and fauna, including rare and endangered species, is given, and the results of the National Center for Biotechnology in this area are summarized.